Skin tear prevention: what Is “usual” skin moisturising practice? - Newall, Tracy (Nelly) (Curtin University, 2014)
This study was an adjunct to a randomised controlled trial (RCT) to test whether skin moisturising reduced the incidence of skin tear development.Staff surveys and interviews identified that there was ad hoc moisturising practice pre-intervention while post-intervention “usual”’ practice matched the intervention protocol at just the intervention sites. This finding therefore allowed the RCT to conclude that the lower skin tear incidence found in the intervention sites could be attributed to the moisturising protocol.